The effect of optimum microosteoperforation accelerated tooth movement on mandibular trabeculae bone volume fraction – a randomized controlled trial / Teh Ng Heng Khiang - Teh, Ng Heng Khiang (2019)
Objective: To investigate the effect of Micro-osteoperforation (MOP) on the horizontal and vertical distribution of mandibular trabeculae pattern in relation to different MOP intervals on canine retraction. Method: This was a split-mouth randomized clinical trial of thirty participants equally randomized into three groups of different MOP intervals (four, eight and twelve weekly). Cone Beam Computed Tomography (CBCT) images (70kV, 10mA, 10.80 seconds, field of view (FOV) of 5cm x 5cm and voxel size of 76µm) were taken to assess the bone volume fraction (BV/TV) in horizontal and vertical planes. Results: BV/TV was significantly reduced (mean difference 9.79%, SD 11.89; 95% CI of 4.77 - 14.81; p = 0.00) and canine retraction significantly increased (mean difference -1.25mm/4months, SD 0.79; 95% CI -1.59 - - 0.92; p = 0.00) at MOP sites as compared to control sites. MOP significantly changed the vertical and horizontal patterns of trabeculae bone with lower BV/TV in the areas nearest to intervention, as compared to the control sites. Only the 4 weekly MOP interval group showed significant decrease in BV/TV (mean difference 14.73% SD 12.88; 95%; CI 3.96 – 25.50; p = 0.01) despite significant increase in canine retraction rate for all interval groups. With the use of MOP, BV/TV was found to be inversely correlated to the rate of canine retraction (r = -0.425; p = 0.039). Conclusions: There is a moderate inverse relationship of a significant reduction of bone volume fraction as canine retraction rate significantly increased. The bone volume fraction reduction was found significant for the four weekly MOP interval, and has not been proven to extend beyond the interdental region of the intervention. iv Keywords: accelerated tooth movement; micro-osteoperforation; bone volume fraction; BV/TV